Internal friction peculiarities in metals subjected to a single weak magnetic field pulse - Datsko, O.I.; Abramov, V.S.; Dmitrenko, V.Yu.; Chishko, V.V. (Functional Materials, 2004)
Behavior of low-frequency internal friction level in various metals during first few minutes after exposure to weak magnetic field pulse has been studied. The time dependence of internal friction during the first 10 to 15 min has been found to exhibit a maximum in some cases and a minimum in other ones. This fact is related to differences in irregular distributions of tensile and compressive internal stresses in the samples un der investigation along their axes. Исследовалось поведение уровня низкочастотного внутреннего трения в различных металлах в первые минуты после воздействия на них импульса слабого магнитного поля. Установлено, что временная зависимость внутреннего трения на протяжении 10-15 минут обнаруживает в одних случаях максимум, а в других — минимум. Этот результат связывается с различным неравномерным распределением сжимающих и растягивающих внутренних напряжений в материалах исследуемых образцов вдоль их оси. Досліджено повєдінку рівня низькочастотного внутрішнього тертя у різних металах у перші хвилини після впливу на них імпульсу слабкого магнітного поля. Встановлено, що часова залежність внутрішнього тертя на протязі 10-15 хвилин має в одних випадках максимум, а в інших — мінімум. Цей результат пов’язується з різним нерівномірним розподілом стискаючих та розтягуючих внутрішніх напружень у матеріалах зразків, що досліджувалися, впродовж їх осі.